Investigation on Strength Characteristics of Geopolymer Concrete with M-Sand and Construction Waste - Deepapriya, S; Saravanan, E; Ruthresh Kumaran, M; Prashanth, G (International Journal of Engineering and Technology, 2018)
Geopolymer concrete are totally inorganic based ceramic that balanced by oxide. The manufacturing of ordinary Portland cement contributesÂ 5 -7% of total greenhouse gas by reducing Co2 emission. It also consumes large amount energy. Hence it is essential to find alternative to cement. silica fume is an ultrafine powder product collected by ferrosilicon and silicon alloy production. It alumina and silica are also rich. In this furnace slag, fly-ash, silica fume is material are used to manufacture a geopolymer concrete. Geopolymer material be caused by reaction obtain from source material are silica and alumina with alkaline solution. Geopolymer is a completely replacing material of cement. Geopolymer (fully replacing) construction waste (10%, 15%, 20% replacing)) and alkaline activator undergo geopolymerization process to produce alumino silicate gel. Alkaline solution is a mix of sodium silicate and sodium hydroxide with relative amount (2.0). A grade has selected for the investigation were M30.The mix were designed.Â Â